Translating health and healing in things fall apart (TFA) and arrow of God (AOG) into German: an intercultural communication appraisal (2021)
The knowledge about a people that engenders attitudes and responses towards them come mostly from knowing diverse aspects of their culture. This knowledge can be accessed through various textual media including translated literary texts. The world of diseases, ill-health and healing of a people, the Igbo in this instance, mirrors aspects of the cultural landscape of world-views, values and belief systems that not only determine the attitudes and relationships within the culture regarding well-being but also shape how the people may be perceived as an African cultural identity. Differences and distance between cultures, asymmetry in cultural attitudes and relations plus the cultural competence of the translator would affect adequacy in the transfer of meanings of health contexts, terms and concepts in translation and thus determine the quality of representation of a people. Employing intercultural textual and translation analysis and illustrating with purposively selected translated text units from the German translations of Chinua Achebe’s novels Things Fall Apart (TFA) and Arrow of God (AOG), this paper concludes, following observed misrepresentations of the source culture, with emphasis on sufficient knowledge of the interrelating source and target cultures and a thorough understanding of particular contexts of cultural meanings as translator base knowledge that will facilitate adequate transfer of meanings and make intercultural understanding and representation feasible through translation.